2021
DOI: 10.1186/s40703-021-00163-2
|View full text |Cite
|
Sign up to set email alerts
|

Physical modeling of the long-term behavior of integral abutment bridge backfill reinforced with tire-rubber

Abstract: The primary objective of this study is to investigate the benefits of adding tire rubber as an inclusion to backfill behind integral bridge abutments. In this respect, four physical model tests that enable cyclic loading of the backfill-abutment are conducted and evaluated. Each test consisted of 120 load cycles, and both the horizontal force applied to the top of the abutment wall and the pressures along the wall-backfill interface is measured. The primary variable in this study is the tire rubber content in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The effective length was defined as the pile length below the excavation surface. The soil used in the model test is sandy silt with a dry density of 1.53 g/cm 3 . The soil mechanical and physical properties are summarized in Table 3.…”
Section: Case Fourmentioning
confidence: 99%
See 2 more Smart Citations
“…The effective length was defined as the pile length below the excavation surface. The soil used in the model test is sandy silt with a dry density of 1.53 g/cm 3 . The soil mechanical and physical properties are summarized in Table 3.…”
Section: Case Fourmentioning
confidence: 99%
“…The pile uplift capacity before and after excavation was 17,000 kN and 12,000 kN, respectively, showing a 29% capacity loss caused by the excavation. The soil used in the model test is sandy silt with a dry density of 1.53 g/cm 3 . The soil mechanical and physical properties are summarized in Table 3.…”
Section: Case Fourmentioning
confidence: 99%
See 1 more Smart Citation
“…Frontiers in Built Environment frontiersin.org inclusion (e.g., EPS foam, tire shred, or tire-derived aggregates) has been placed between the abutment and the backfill to reduce the horizontal earth pressures behind the abutment and the pile moment (Hoppe, 2005;Caristo et al, 2018;Duda and Siwowski, 2020;Liu et al, 2021a;Zadehmohamad et al, 2021). Arsoy (2000) indicated that flexible piles were beneficial to prevent damages of pileabutment connections.…”
Section: Figurementioning
confidence: 99%
“…If bridges are regularly inspected and repaired, disasters can be avoided. The use of renewable materials such as tire rubber [2] in bridge damage can effectively improve its performance. Therefore, bridge damage detection and assessment have gradually become a popular research direction.…”
Section: Introductionmentioning
confidence: 99%